Tejiendo Sabiduría - Karsin, Nicole (United States, 2012)
In Colombia’s war-torn indigenous villages, three brave women from distinct tribes use nonviolent resistance to defend their peoples’ survival. Trapped in a protracted predicament that is fueled by the drug trade, native women are resourcefully leading and creating transformation imbued with hope. The film bears witness to neglected human rights catastrophes and interweaves character-driven stories about female empowerment, unshakable courage, and faith in the endurance of indigenous culture.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films